EFFECT OF USING TABOO GAME TO NINTH GRADERSâ SPEAKING SKILL - Susilo, Yusup Kuncoro Bowo (Jurnal Dinamika Pendidikan, 2014)
This study was conducted to improve the ninth gradersâ speaking skill. To attain the objective, an experiment was conducted at SMP Pangudi Luhur Jakarta. Thirty five students in the control group were taught speaking in the conventional way, while the thirty nine students in the experimental group were taught by using taboo game. The data collected using tests in both groups were analyzed by using SPSS 15.0 program. The results revealed that there was a significant effect of the implementation the taboo game to the ninth year studentsâ speaking skill. It was indicated by the result of the statistical calculation that the tcount (=19.395) > ttable (=1.992) with sig. level (=0.05) and d.f (=76). Through the calculation the Ho was rejected and Ha was accepted. Based on the findings, it was concluded that taboo game was significantly effective to improve studentsâ speaking skill.Keywords : taboo game, speaking skill